3D TECHNOLOGY AS A MODERN METHOD FOR STUDYING AND USING THE BUKHARA SHRINE (Spectrum Journal of Innovation, Reforms and Development, 2025)
Uzbekistan, with its rich cultural and spiritual heritage, memory and fine arts, historical monuments, as well as many world-famous famous and great ancestors such as Muhammad ibn Ismail al-Bukhari, Muhammad Musa al-Khwarizmi, Abu Nasr al-Farabi, Ahmad al-Farghani, Abu Ali ibn Sina, Abu Rayhan al-Biruni, Ahmad Yassawi, Abu Isa al-Termizi, Mirza Ulug'yek, Bahauddin Naqshband, Abdulkhaliq G'ijduvani, Khoja Ali Romitani, Amir Temur, Alisher Navoi, Babur, continues to attract world scholars and tourists. This, in turn, increases our unique place and influence in international tourism markets.